Overexpression of genes of glycolytic pathway enzymes in cancer cells - Gustavo F., Gustavo F. (2024)
Cancer is an important cause of mortality worldwide and the number of people who are affected by it is increasing. It is known that cancer cells have greater glycolytic activity compared to normal cells. This is due to overexpression of genes which codify enzymes involved in this metabolic pathway. This aberrant metabolism allows cancer cells to proliferate quickly while using a constant source of energy. Through this, cancer cells have a significant advantage over normal tissue cells. The functional importance of glycolysis in cancer is widely accepted, but little is known about the influence of gene expression of this metabolic pathway working at high rates. In this review we compile information on the overexpression of genes codifying glycolytic pathway enzymes in cancer cells, determine which are the enzymes involved and describe some of the techniques applied in the study of gene overexpression.